1977
DOI: 10.1136/jcp.30.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomembranous colitis.

Abstract: Three basic histopathological patterns which may be seen in rectal biopsies from patients with pseudomembranous colitis are described, based on a study of 29 cases. The spectrum of change is illustrated and the problems of differential diagnosis are discussed--from a non-diagnostic proctitis at one extreme to acute ischaemia at the other. In the differential diagnosis of the acute colitic, the importance of urgent rectal biopsy and a carefully taken drug history is stressed. The association of pseudomembranous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
14

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(69 citation statements)
references
References 28 publications
1
54
0
14
Order By: Relevance
“…This finding is ofpotential importance, as it has variously been suggested that the intestinal lesions associated with pseudomembranous colitis in humans may be due to a primary endothelial effect (5) and that the toxin A effects on rabbit ileum are secondary to toxin-stimulated release of mediators from inflammatory cells (6). The most striking effect oftoxin A on Ts4 (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is ofpotential importance, as it has variously been suggested that the intestinal lesions associated with pseudomembranous colitis in humans may be due to a primary endothelial effect (5) and that the toxin A effects on rabbit ileum are secondary to toxin-stimulated release of mediators from inflammatory cells (6). The most striking effect oftoxin A on Ts4 (17).…”
Section: Discussionmentioning
confidence: 99%
“…is primarily affected by C. dificile toxins. Based on analysis of human rectal biopsies displaying pseudomembranous colitis in the early phase, Price and Davies (5) speculated that the initial target might be the endothelium lining the superficial capillary network. In this view, the epithelial effects would be a secondary event.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of PMC are associated with antibiotic use, although 1–7% of cases of PMC have had no documented antibiotic exposure [34]. PMC has been reported in patients without antibiotic exposure who have insulin-dependent diabetes mellitus, hepatic and renal failure, malnutrition, cystic fibrosis or have had upper GI tract surgery [61].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Ischemic colitis may also exhibit a yellow confluent pseudomembrane [30]. Histologic findings include epithelial necrosis, distended goblet cells, infiltration of the lamina propria with leukocytes, and plaques consisting of inflammatory cells, fibrin and mucin [10, 24, 34, 35](fig. 2a, b).…”
Section: Diagnosismentioning
confidence: 99%
“…Histologically, the pseudomembranes, composed of fibrin, mucus, epithelial and inflammatory cells appear as "clouds" rising from points of superficial ulcerations. The lesions have been termed "volcano" lesions appearing like an eruption above underlying glandular lesions [47] . In 22% of cases, pseudomembranes were visualized on endoscopy, but not present histologically [48] .…”
Section: Endoscopic Diagnosis Of CDImentioning
confidence: 99%